A Smart Heating System Based on Integrated Renewable Energy Sources for Swine Nursery Buildings - Stefano Benni; Carlos Alejandro Perez Garcia; Marco Bovo; Alberto Barbaresi; Francesco Tinti; Alexander Loris; Iván P. Acosta-Pazmiño; Panteleimon Bakalis; Patrizia Tassinari; Daniele Torreggiani (Energies)
The control of environmental parameters in livestock farming is essential to achieve optimal ranges of temperature and humidity. HVAC systems for this purpose are characterized by high energy demands, causing significant GHG emissions when relying on fossil fuels. The aim of this study is the development and testing of a sustainable heating system for a nursery barn hosting 2500 weaners, as well as the assessment of the effectiveness and the performance of the new system. This work involved the implementation of a renewable energy source (RES) system incorporating a borehole thermal energy storage and photovoltaic thermal collectors, integrated with a Dual-Source Heat Pump. A smart control system was installed and the collected data were processed to define the optimal settings of the integrated plant for energy production and efficiency. The performance in terms of the control of the environmental conditions of the nursery barn was assessed on the basis of the environmental parameters analyzed, with particular reference to the animal-occupied zones. The results showed that a mix of RESs can be properly defined and integrated in an automated heating system to meet the specific requirements of a swine farm, thanks to a project specifically designed to exploit the renewable resources typically available in farming environments.